Photocatalytic hydrogen production over titania modified by gold – Metal (palladium, nickel and cobalt) catalysts. (28th December 2016) - Barrios, C.E.; Albiter, E.; Gracia y Jimenez, J.M.; Tiznado, H.; Romo-Herrera, J.; Zanella, R.
Abstract: The photocatalytic production of hydrogen on modified Au/TiO2 -based photocatalysts by using water/methanol mixtures was studied. The main goal was to study the effect of surface modification of Au/TiO2 with Pd, Ni and Co on H2 production under UV light irradiation ( λ ca . 254 nm). Catalysts were produced by depositing Pd, Ni or Co precursors (nitrates hydrated salts) on TiO2 (Evonik, P25) by incipient wetness impregnation followed by thermal treatment under H2 (Pd and Co) or air (Ni). Thereafter, Au was incorporated by deposition-precipitation with urea (DPU method) and then the catalysts were thermally activated again under air flow. The photocatalysts were characterized by UV–Vis diffuse reflectance, HAADF-TEM, EDXS, FTIR CO adsorption, XPS and photoluminescence. In order to obtain detailed information about the composition of the nanoparticles, high-resolution elemental analyses (EDXS line scans) were performed. The Au-Pd, Au-Ni and Au-Co on TiO2 photocatalysts showed higher performance for H2 production (266, 256 and 171 mmol H2  mmolAu −1  h −1, respectively) compared to the Au/TiO2 material (106 mmol H2  mmolAu −1  h −1 ). PL results showed that the improved H2 production rate could be explained by an enhanced charge separation. The highest H2 production showed by the Au-Pd/TiO2 sample could be attributed to synergistic effects, derived from the interaction between Au and Pd particles. For the Au-Ni/TiO2 and Au-Co/TiO2 samples it is proposed that nickel or cobalt oxides worked as promoters (with additives effects) because of the formation of a p–n heterojunction. Graphical abstract: Highlights: Surface modified TiO2 with Pd and Au showed a synergistic effect for H2 production. TiO2 modified with Pd and Au hinder electron–hole recombination. The p–n heterojunctions of Ni or Co oxides with TiO2 promotes H2 production. High dispersion of NiO NPs improves the charge transfer of electrons to produce H2 .